Insider Trading in Germany - Do Corporate Insiders Exploit Inside Information? - Björn M. Dymke; Andreas Walter (BuR - Business Research, 2008)
Our study focuses on the question whether corporate insiders in Germany exploit inside information while trading in their companys stock. In contrast to prior international studies, which are not able to link insider transactions to a formal definition of inside information, we relate insider transactions to subsequent releases of inside information via ad-hoc news disclosures. We find evidence that corporate insiders as a group seem to trade on inside information. Moreover, members of the supervisory board seem to be most active in exploiting inside information, since they realize exceptionally high profits with their frequent front-running transactions.
urn:nbn:de:0009-20-16524
Keywords: 650; finance; Insiderhandel; Informationsverhalten; Finanzmarktaufsicht; Deutschland